Analysis of the Effect of USD/IDR Exchange Rate, Inflation, BI Rate, KOSPI, SCI, And S&P500 Index on IHSG - Ardy Ganda Mahardika (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study examines the influence of six factors - USD/IDR Exchange Rate, Inflation, BI Rate, KOSPI Index, SCI Index, and S&P500 Index - on the Jakarta Composite Index (JCI) on the Indonesia Stock Exchange over the period 2018-2023. This research employs a quantitative approach. The data used in this study are weekly time series secondary data obtained from the official IDX website, Bank Indonesia, and other foreign stock price index websites. This study utilizes a causality research design and employs parametric statistical test analysis tools to test and analyze the magnitude of the influence of the independent variable on the dependent variable. The data analysis used in this research is multiple regression. The results showed that the USD/IDR exchange rate has a significant negative effect on the JCI. A weakening of the Rupiah against the US Dollar tends to have a negative impact on the JCI. In contrast, Inflation, BI Rate, KOSPI Index, SCI Index, and S&P500 Index have a significant positive effect on the JCI. This means that an increase in inflation, BI Rate, and foreign stock indices tends to boost the JCI. The findings suggest that the JCI is influenced by a variety of internal and external factors. The weakening of the USD/IDR exchange rate, although having a negative influence, can be interpreted as a potential increase in export competitiveness, foreign capital inflows, and profits of exporting companies. This, in turn, has a positive impact on the JCI.